2006
DOI: 10.1002/mame.200600120
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Properties of Novel Poly(urethane‐imide) Networks as Electrical Insulators with Improved Thermal Stability

Abstract: Summary: A new series of thermoplastic poly(urethane‐imide)s (TPUI1‐4) containing hydroxyl groups in the backbone was synthesized from the reaction of epoxy‐terminated polyurethane prepolymers (EPU1‐4) and an imide containing diacid (DIDA) chain extender under optimized reaction conditions. EPU1‐4 was prepared through end‐functionalization of NCO‐terminated polyurethanes based on polyester polyol (CAPA) and hexamethylene diisocyanate with glycidol. A blocked isocyanate (BIC) was made from the reaction of trime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…3. Sample Ba/EPU(0/100) shows two thermal transitions at about 2378C, attributed to a type transition as well as another one at 508C due to the melting of crystalline region arose from polycaprolactone moiety of EPU [31]. As it is clear from Fig.…”
Section: Viscoelastic Propertiesmentioning
confidence: 81%
See 1 more Smart Citation
“…3. Sample Ba/EPU(0/100) shows two thermal transitions at about 2378C, attributed to a type transition as well as another one at 508C due to the melting of crystalline region arose from polycaprolactone moiety of EPU [31]. As it is clear from Fig.…”
Section: Viscoelastic Propertiesmentioning
confidence: 81%
“…The current study is in continuation of our ongoing researches on the preparation of polyurethane based electrical insulators with enhanced thermal, mechanical, and electrical properties [31,32]. The polymeric films were prepared through thermal treatment of the blends made from an epoxy-terminated polyurethane prepolymer (EPU) and different amounts of bisphenol-A based benzoxazine monomer.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that imide polymers and copolymers are a well-established class of polymers that show good properties to increase the crystallization, thermal stability and mechanical properties (12)(13)(14). Hence, the improvement in the thermal and mechanical properties of PUs through incorporation of imide groups into the backbone to prepare poly (urethane-imide)s have been reported by numerous researchers (9,(15)(16)(17). In view of the imide unit modified mechanical property of PUs, introduction of the imide unit into PEEs to prepare poly(ester-ether-imide)s (PEEIs) to improve the compatibility between soft segments and hard segments was reported by Kricheldorf and in our previous literature (10,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 98%
“…To improve the thermal stability of TPUs, many methods have been attempted over the years 3–5. One of the accepted approaches is chemical modification of the structure by copolymerization with thermally stable polymers.…”
Section: Introductionmentioning
confidence: 99%